HOW TO TRAGICALLY DECEIVE YOURSELF - Ohlhorst, Jakob (Les ateliers de l'éthique / The Ethics Forum, 2018)
This paper introduces the concept of tragic self-deception. Taking the basic notion that self-deception is motivated belief against better evidence, I argue that there are extreme cases of self-deception even when the contrary evidence is compelling. These I call cases of tragic self-deception. Such strong evidence could be argued to exclude the possibility of self-deception; it would be a delusion instead. To sidestep this conclusion, I introduce the Wittgensteinian concept of certainties or hinges: acceptances that are beyond evidential justification. One particular type of certainties—iHinges, which are adopted for motivational reasons—explain the phenomenon of tragic self-deception: they warrant the subject’s dismissal of the evidence without loss of rationality from the subject’s point of view. Subsequently, I deal with some objections that can be raised against this account of self-deception.